Potent Melanin Production Enhancement of Human Tyrosinase Gene by Tat and an Entrapment in Elastic Cationic Niosomes: Potential Application in Vitiligo Gene Therapy - Manosroi J. (2014)
Potent melanin production enhancement of human tyrosinase plasmid (pAH7/Tyr, P) in mouse melanoma cells (B 16F 10) by Tat peptide (T) and an entrapment in elastic cationic niosomes (E) was described. The E composed of Tween 61/cholesterol/dodecyl dimethyl ammonium bromide at 1:1:0.5 molar ratio was prepared by freeze-dried emptying liposomes method. PE at P/E ratio of 1:160 w/w and TPE at T/P/E ratio of 0.125:1:160, 0.25:1:160, and 0.5:1:160 w/w/w were prepared. The final concentration of the plasmid in the study was 4ng/μL. By sulforhodamine B assay, PE and TPE complexes showed slight or no cytotoxic effect. The cells transfected with TPE (0.5:1:160) exhibited the highest enhancement of tyrosinase enzyme activity of 11.82-, 7.67-, 5.07-, and 6.29-folds of control, P, PE, and TP (0.5:1) and melanin production of 13.03-, 8.46-, 5.36-, and 6.58-folds of control, P, PE, and TP (0.5:1), respectively. The elastic cationic niosomes demonstrated an increase in thermal stability of P at 4±2, 25±2, and 45±2°C. The vesicular size and the zeta potential values of PE and TPE complexes were slightly increased but still in the range of stable dispersion (out of ±30mV). These results indicated the high potential application of the TPE complexes for further investigation for vitiligo gene therapy. TPE complexes exhibited potent enhancement of tryosinase gene expression and melanin production in melanoma cell line (B 16F 10). This result indicated the high potential application of the TPE complexes for further investigation for vitiligo gene theraphy. © 2012 John Wiley & Sons A/S.